2020
DOI: 10.1080/00207543.2020.1724341
|View full text |Cite
|
Sign up to set email alerts
|

Pricing decision with conspicuous customers: quick responses versus value-added services

Abstract: In order to eliminate the negative effects of customer strategic behavior, retailers often adopt quick response or value-added services. While in a luxury market with conspicuous customers, retailers' pricing decisions of these two strategies become more complicated. This paper studies a supply chain with a retailer serving a mixture of conspicuous and ordinary strategic customers. We develop three models so that the retailer provides i) neither quick response nor value-added services;ii) only quick response; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Hong et al [48] studied how value-added service influences profits and decisions in a closed-loop supply chain. Liu et al [49] studied the impacts of conspicuous customers on quick response and value-added service by pricing and strategy comparisons in a luxury market. Begen et al [50] showed that when cooperative advertising solutions exist, the information sharing of value-added service between the traditional retailer and the manufacturer will result in a win-win situation, and it will also benefit the whole supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hong et al [48] studied how value-added service influences profits and decisions in a closed-loop supply chain. Liu et al [49] studied the impacts of conspicuous customers on quick response and value-added service by pricing and strategy comparisons in a luxury market. Begen et al [50] showed that when cooperative advertising solutions exist, the information sharing of value-added service between the traditional retailer and the manufacturer will result in a win-win situation, and it will also benefit the whole supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consumers pay more and more attention to CSR, which has been a new competitiveness for the enterprises (Liu et al, 2020). Research on the implementation of CSR by CLSC companies has received considerable attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also important for companies to provide value‐added services while undertaking CSR. Value‐added services can increase the value and willingness of customers to purchase (Liu et al, 2020). Kastalli and van Looy (2013) studied that service business scale and profit margin present in nonlinear positive correlation.…”
Section: Introductionmentioning
confidence: 99%